The Arab Spring abroad : diaspora activism against authoritarian regimes - Moss, Dana M. (Cambridge studies in contentious politics., 2022)
The Arab Spring revolutions of 2011 sent shockwaves across the globe, mobilizing diaspora communities to organize forcefully against authoritarian regimes. Despite the important role that diasporas can play in influencing affairs in their countries of origin, little is known about when diaspora actors mobilize, how they intervene, or what makes them effective. This book addresses these questions, drawing on over 230 original interviews, fieldwork, and comparative analysis. Examining Libyan, Syrian, and Yemeni mobilization from the US and Great Britain before and during the revolutions, Dana M. Moss presents a new framework for understanding the transnational dynamics of contention and the social forces that either enable or suppress transnational activism. This title is also available as Open Access on Cambridge Core.